2020
DOI: 10.3390/ijms21103600
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic Vsx1 Plays a Key Role in Defining V2a Interneuron Sub-Lineage by Directly Repressing tal1 Transcription in Zebrafish

Abstract: In the spinal cord, excitatory V2a and inhibitory V2b interneurons are produced together by the final division of common P2 progenitors. During V2a and V2b diversification, Tal1 is necessary and sufficient to promote V2b differentiation and Vsx2 suppresses the expression of motor neuron genes to consolidate V2a interneuron identity. The expression program of Tal1 is triggered by a Foxn4-driven regulatory network in the common P2 progenitors. Why the expression of Tal1 is inhibited in V2a interneurons at the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…EV3A ). Meanwhile, the mRNA expression levels of forebrain marker fezf2 (Shimizu and Hibi, 2009 ), dopaminergic neurons marker sim1a and th (Schweitzer et al, 2013 ), GABAergenic neuron marker gad1b (Zhang et al, 2020 ) did not differ significantly but showed a decreasing trend (Fig. EV3C ).…”
Section: Resultsmentioning
confidence: 95%
“…EV3A ). Meanwhile, the mRNA expression levels of forebrain marker fezf2 (Shimizu and Hibi, 2009 ), dopaminergic neurons marker sim1a and th (Schweitzer et al, 2013 ), GABAergenic neuron marker gad1b (Zhang et al, 2020 ) did not differ significantly but showed a decreasing trend (Fig. EV3C ).…”
Section: Resultsmentioning
confidence: 95%
“…Embryo whole mount in situ hybridization was adapted from (Thisse and Thisse, 2008). The gad1b riboprobe encompassing the nucleotides 1104-2334 of accession noAB183390 as described in (Zhang et al, 2020) was used. The gad1b template was generated by PCR amplification by adding the T7 promoter sequence (indicated by capital letters) to the reverse primer ( gad1b Fw 5’— gat ggt tgc gcg gta taa —3’; gad1b Rev 5’— ata tta ata cga ctc act ata gCT TCG TTA AAA GGG TGC —3’).…”
Section: Methodsmentioning
confidence: 99%
“…The TF gene vsx1 has been identified as essential for the development of V2a interneurons, and its inhibition leads to an increase in V2b cells expressing tal1 . Vsx1 represses tal1 expression by directly binding to its cis‐regulatory sequence (Table 2) [82].…”
Section: Neural Specification—the Case Of the Zebrafish P2 Domainmentioning
confidence: 99%